The copy workshop workbook - Bendinger, Bruce (1993)
Los temas principales de este texto son: The strategy, selling ideas, sales power, how to write with style, typing y typography, sound advice radio, a quick course in comedy, television, tvproducyion y terminology and supervision
Incl. Next Steps p. 379-381; Words p. 382-391; some number
Keywords: Marketing; Publicidad